1999
DOI: 10.1111/1467-9450.404131
|View full text |Cite
|
Sign up to set email alerts
|

The role of parents' self‐esteem, mastery‐orientation and social background in their parenting styles

Abstract: In order to examine the extent to which parents' levels of education, financial resources, self-esteem, and their mastery-orientation versus task-avoidance are associated with their parenting styles and parental stress, data from two studies were analyzed. In Study I, parents of 105 6 to 7-year old children were asked to fill in scales measuring their parenting styles and parental stress, mastery-orientation, financial resources, and their level of education. In Study II, 235 parents were asked to fill in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 41 publications
6
66
0
5
Order By: Relevance
“…In addition, Aunola et al (1999) found that parents' socioeconomic background in a Finnish population was related to more authoritarian parenting strategies and to less positive parenting. This suggests that one's social background can be influential in parenting behaviors.…”
Section: Socio-cultural Influencesmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, Aunola et al (1999) found that parents' socioeconomic background in a Finnish population was related to more authoritarian parenting strategies and to less positive parenting. This suggests that one's social background can be influential in parenting behaviors.…”
Section: Socio-cultural Influencesmentioning
confidence: 98%
“…Parental Self-Esteem and Self-Efficacy It is also important to consider parental self-esteem as parents with higher levels of self-esteem are likely to engage in more positive parenting strategies such as expression of affection, rational guidance, encouragement, and supervision (Aunola et al 1999). Mothers who are at higher-risk for abuse have shown decreased levels of selfesteem and self-efficacy (Teti and Gelfand 1991).…”
Section: Perceived Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-and long-term impacts of the transition to parenthood on mothers' self-esteem and relationship satisfaction may have consequences for the lives of mothers, fathers, and their children. Both self-esteem and romantic relationship satisfaction have been associated with psychological adjustment (Dush & Amato, 2005;Orth, Robins & Widaman, 2012), positive parenting behavior (e.g., Aunola, Nurmi, Onatsu-Arvilommi, & Pulkkinen, 1999;Kitzmann, 2000) and beneficial influence on child development (e.g., Davies & Cummings, 1994;Grych & Fincham, 1990;Jones & Prinz, 2005). These findings stress the importance to study how selfesteem and relationship satisfaction develop across the transition to parenthood.…”
mentioning
confidence: 93%
“…Their key components include: (1) psycho-education about underlying maladaptive parental thinking patterns; (2) parental emotional self-regulation; (3) adaptive parental communication styles in interactions with their child; and (4) an emphasis on controlling children's externalizing behaviors. It is thought that the latter, such as temper tantrums, can be better managed through consistency in responding and correctly applied time-out (Aunola & Nurmi, 2005; Centers for Disease Control and Prevention [CDC], 2009;Tully, 2008;Wade, Macvean, Falkiner, Devine, & Mildon, 2012). All of these together should, in the longer term, improve outcomes for parent and child.…”
mentioning
confidence: 99%